Biomechanical behavior of pericardial human tissue: A constitutive formulation. (September 2014) - Pavan, Piero G; Pachera, Paola; Tiengo, Cesare; Natali, Arturo N
This work aims to present a constitutive model suitable to interpret the biomechanical response of human pericardial tissues. The model is consistent with the need of describing large strains, anisotropy, almost incompressibility, and time-dependent effects. Attention is given to human pericardial tissue because of the increased interest in its application as a substitute in reconstructive surgery. Specific, even limited, experimental investigation has been performed on human samples taken from surgical grafts in order to verify the capability of the constitutive model in supplying a correct description of tissue mechanical response. Experimental data include uni-axial tensile tests and stress relaxation tests up to 300 s, developed along different directions of the tissue. The grafts tested show different mechanical characteristics for what concern the level of anisotropy of the tissue. The constitutive model proposed shows to adapt to the different configurations of the human pericardium grafts, as emerged by experimental data considered, and it is capable to describe the variability of the mechanical characteristics.